Curriculum innovation model for systemic planning in primary education - Gonzales Cubas, Humberto (2018)
The intention of the scientific article promotes the application of a model of curricular innovation in the systemic planning at the level of primary education; Which has been inspired by the observation of the curricular levels applied in the classroom, such as: annual programming, didactic units and sessions proposed in the institutional educational project-PEI-; Teachers have difficulties in their planning to address the interests, problems and situations of their own context of: • The treatment of competencies, capacities and attitudes. • The selection of the thematics, related to the development of the competencies. • Curricular diversification. • The contextualisation of curricular contents and the demand for their experiential reality. Faced with which it brings that the students do not develop: the concrete logical thought own in the Primary education; the critique -valuation for coexistence and the development of the competences required in the current curricular framework. Given this situation, we worked with the following hypothesis: If a model matrix of competencies is designed, then, the teachers of Regular Basic Education of the Primary Level will be able to overcome their difficulties in the planning of the curricular levels, for which our systemic model will be will articulate with the curricular models DCN of the Ministry of Education, the regional curricular project and the institutional project, through a matrix of competences. Theoretically, the variables of our study have been analyzed from the contributions of the Curricular Theory of systems and the Curricular Plan of Regular Basic Education of the Primary Level. Methodologically we have worked with the teachers of the primary level, in the Educational Institution N ° 11517, Santa Ana in the district of Tumán, province of Chiclayo, Lambayeque region.